Investigating academic resilience in learning English: an ecological context of undergraduate students - Faiza Liaqat; Muhammad Islam; Muhammad Umer Azim; Ahmad Sohail Lodhi (Frontiers in Psychology)
Despite a general understanding of the role resilience may play in students’ wellbeing and learning growth, there has been little or no focus on examining the resilient attitude of undergraduate L2 learners from Lahore, Pakistan. Students from various linguistic and cultural backgrounds are drawn to Lahore because it is a hub for higher education in Pakistan with almost 28 public and private sector universities. This quantitative study collected data from 498 undergraduate students from various academic disciplines and ethnic backgrounds studying in the universities of Lahore. The study utilized a survey questionnaire on Student AR in English Learning Scale, adapted to align with Bronfenbrenner’s Ecological System Theory. The study conducted statistical analyses, including Regression Analysis, one-way ANOVA, descriptive statistics, and frequency counts, to gain results. The findings underscored an important role of ecological factors, such as self-esteem, teacher support, peer support, and problem solving, which contributed significantly to the AR of participants. In addition, the findings also suggest that Baloch students exhibited lower scores across multiple dimensions of AR and social support as compared to all other ethnic groups, including Pashtun, Punjabis, Sindhi, and Saraiki. This research contributes to the understanding of resilience dynamics within a multicultural English language learning context and highlights the need to provide cultural sensitivity training to teachers and students in order to foster inclusive language learning environments.